Electrospun TPU Nanofibrous Membranes Incorporating Ciprofloxacin-Montmorillonite Nanoclays for Sustained Drug Release and Wound Healing - Caliskan, Tugce; Doymus, Burcu; Onder, Sakip; Kayaoglu, Burcak Karaguzel; Gocek, Ikilem (WILEY, 2026)
This study aimed to develop electrospun thermoplastic polyurethane (TPU) membranes incorporating ciprofloxacin (CIP)-loaded montmorillonite (MMT) nanoclays to achieve controlled antibiotic release for wound healing applications. CIP was intercalated into MMT and then dispersed homogeneously within the TPU matrix to fabricate nanofibrous membranes via electrospinning. Structural and chemical analyses using X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) confirmed successful drug intercalation and interactions among CIP, MMT, and TPU. Morphological characterization by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) revealed uniform, bead-free fibers with well-dispersed additives. Drug release studies showed that CIP-loaded MMT membranes exhibited significantly slower and sustained release (12.4%-20.8% over 6 days) compared to membranes with CIP directly embedded in TPU (59.1%-73.4%), indicating effective modulation of release kinetics by MMT. Cytotoxicity tests on 3T3 fibroblasts demonstrated good biocompatibility of pure TPU membranes (> 85% viability), while MMT-containing membranes showed reduced cell viability over time, suggesting potential dose-dependent effects. Antibacterial assays confirmed that only CIP-containing membranes inhibited Staphylococcus aureus and Escherichia coli growth, with no activity observed in pure TPU or TPU/MMT controls. Overall, the results indicate that CIP-loaded MMT electrospun TPU membranes provide a promising platform for sustained drug delivery and antibacterial activity in wound dressing applications.
Keywords: antibacterial efficacy; cytotoxicity; drug release; nanoclay; nanofibrous membrane; wound-dressing; ANTIBACTERIAL ACTIVITY; DELIVERY SYSTEMS; NANOCOMPOSITES; SORPTION; INTERCALATION; ADSORPTION; DRESSINGS; Engineering; Materials Science